Distorting Economic Balance and its Consequences on the Regional Market of Consulting Services - Ashirova, Svetlana Anatolievna; Yudina, Svetlana Valentinovna; Kabitova, Yevgeniya Vladimirovna; Garifullina, Mouhabbat Sharifovna; Serikova, Natalia Vladimirovna (International Review of Management and Marketing, 2016)
At the present time on the background of the stagnation of the professional consulting services market, the potential capacity of this market is rather sufficient to be attractive for investments. On the basis of the survey according to the representative selection of consulting companies and representatives of small and medium-sized business of the SE RT (South-East of the Republic of Tatarstan), the spread between the demand and the supply on the regional market of consulting services was revealed. The market of consulting services in Almetyevsk was analyzed. Based on the obtained results, offers on using the potential of the regional market of consulting services and decreasing the stable “spread” between the demand and the supply were presented. Keywords: consulting, machine-building enterprises, marketing strategy, immersed pumping machinery, external markets. JEL Classifications: L10, M31, L64, L84